Improving the Learning Outcomes of Islamic Cultural History of the Prophet Muhammad PBUH's Personality Material Through the Application of the Make A Match Type Cooperative Learning Model at Madrasah Ibtidaiyah - Zakiyah, Nur; Hafini, Hafini (Research Journal on Teacher Professional Development, 2024)
This research aims to improve the learning outcomes of Islamic Cultural History subjects in grade IV students of Madrasah Ibtidaiyah Riyadul Jannah for the 2022/2023 school year through the application of the Make a Match type cooperative learning model. This research is a Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of four stages, namely, planning, implementation, observation, and reflection. The subject of this study is grade IV students of MIS Riyadul Jannah for the 2022/2023 school year with a total of 20 students. The main data collection techniques are carried out by observation and tests, while the supporting techniques are interviews and documentation. Data analysis uses descriptive and qualitative descriptive statistical analysis techniques. The results of the study showed that there was an increase in student learning outcomes in each cycle. The average cognitive learning outcome of students increased from the pre-cycle stage of 61.5 to 73.3 in the first cycle, then increased again to 85.5 in the second cycle. In addition, the percentage of students who achieved learning completeness also increased from 25% in the pre-cycle to 50% in the first cycle, and 95% in the second cycle. Based on the results of this study, it can be concluded that the application of the Make a Match type cooperative learning model is effective in improving student learning outcomes in the Islamic Cultural History subject grade IV MIS Riyadul Jannah for the 2022/2023 school year.